Controlled Pulse Influence in Games with Fixed Termination Time - Ostapenko, E. V.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We construct optimal strategies for players and determine the sets of initial positions favorable for one player or another.